2013
DOI: 10.1021/nn401187c
|View full text |Cite
|
Sign up to set email alerts
|

Au Nanorod Design as Light-Absorber in the First and Second Biological Near-Infrared Windows for in Vivo Photothermal Therapy

Abstract: Photothermal cancer therapy using near-infrared (NIR) laser radiation is an emerging treatment. In the NIR region, two biological transparency windows are located in 650-950 nm (first NIR window) and 1000-1350 nm (second NIR window) with optimal tissue transmission obtained from low scattering and energy absorption, thus providing maximum radiation penetration through tissue and minimizing autofluorescence. To date, intensive effort has resulted in the generation of various methods that can be used to shift th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
351
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(355 citation statements)
references
References 39 publications
3
351
1
Order By: Relevance
“…Similarly, Ag nanowires have been widely exploited as templates for the preparation of hollow nanotubes via the GRR [86,97,[100][101][102][103][104]. Other structures commonly obtained through the GRR between HAuCl 4 and the corresponding Ag template include nanorings [105,106], nanoframes [107][108][109], and nanorattles [110][111][112][113][114]. A set of hollow AuAg nanostructures are shown in Figure 3.…”
Section: Synthesis Of Hollow Nanostructuresmentioning
confidence: 99%
“…Similarly, Ag nanowires have been widely exploited as templates for the preparation of hollow nanotubes via the GRR [86,97,[100][101][102][103][104]. Other structures commonly obtained through the GRR between HAuCl 4 and the corresponding Ag template include nanorings [105,106], nanoframes [107][108][109], and nanorattles [110][111][112][113][114]. A set of hollow AuAg nanostructures are shown in Figure 3.…”
Section: Synthesis Of Hollow Nanostructuresmentioning
confidence: 99%
“…15,16 A great variety of LNPs have been applied in biomedical research, not only for imaging but also for other purposes including drug delivery and in vitro and in vivo photothermal therapies. 17 Quantum dots (QDs), 18,19 gold NPs, 20 carbonbased NPs (C-NPs), 21,22 organic NPs, 23 and rare earth-doped nanocrystals (RENPs) 24 are among the nanoparticle-based fluorescent probes that have been successfully used in biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…The plasmonic properties of gold nanorods allow them to be used in photothermal therapy [1,2], imaging techniques [3,4], theranostics [5,6], sensing applications [7][8][9][10] and optical memories [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…in photothermal therapy [1,2] and photoacoustic imaging [36][37][38]. It was shown that embedding the nanorods into a titaniumoxide matrix [39], or coating with carbon [40] or other materials [7,25] can protect them from shape transformations during heating up to ~690 °C.…”
Section: Introductionmentioning
confidence: 99%